The nanoscaled metal-organic framework ICR-2 as a carrier of porphyrins for photodynamic therapy - Hynek, Jan; Jurík, Sebastian; Koncošová, Martina; Zelenka, Jaroslav; Křížová, Ivana; Ruml, Tomáš; Kirakci, Kaplan; Jakubec, Ivo; Kovanda, František; Lang, Kamil; Demel, Jan (Beilstein journal of nanotechnology, 2018)
Nanosized porphyrin-containing metal-organic frameworks (MOFs) attract considerable attention as solid-state photosensitizers for biological applications. In this study, we have for the first time synthesised and characterised phosphinate-based MOF nanoparticles, nanoICR-2 (Inorganic Chemistry Rez). We demonstrate that nanoICR-2 can be decorated with anionic 5,10,15,20-tetrakis(4-R-phosphinatophenyl)porphyrins (R = methyl, isopropyl, phenyl) by utilizing unsaturated metal sites on the nanoparticle surface. The use of these porphyrins allows for superior loading of the nanoparticles when compared with commonly used 5,10,15,20-tetrakis(4-carboxyphenyl)porphyrin. The nanoICR-2/porphyrin composites retain part of the free porphyrins photophysical properties, while the photodynamic efficacy is strongly affected by the R substituent at the porphyrin phosphinate groups. Thus, phosphinatophenylporphyrin with phenyl substituents has the strongest photodynamic efficacy due to the most efficient cellular uptake.
Keywords: metal-organic framework; photodynamic therapy; porphyrin; phosphinic acid based MOF; singlet oxygen